ANALISIS KOMITMEN ORGANISASI PEGAWAI TERKAIT GAYA KEPEMIMPINAN TRANSAKSIONAL, TRANSFORMASIONAL, DAN DEMOKRATIS (Studi Kasus di Kecamatan Meurah Dua Kabupaten Pidie Jaya) - Suyatno, Dedi; Yusuf, M. (IndOmera, 2026)
This article examines employee organizational commitment based on the implementation of transactional, transformational, and democratic leadership styles. The case study was conducted on 41 employees at the Meurah Dua Sub-district Office in Pidie Jaya Regency, using an associative method with a quantitative approach and statistical data analysis through path analysis. The findings indicate that: (1) organizational commitment is directly and indirectly influenced by the implementation of a transactional leadership style by 39.82%. (2) The implementation of a transformational leadership style also has a direct and indirect impact on employee organizational commitment by 53.2%. (3) There are direct and indirect effects of democratic leadership style on organizational commitment by 50.97%. (4) The three factors studied—transactional and democratic leadership styles—are causally interconnected and contribute simultaneously to employee organizational commitment by 85.1%.